Keabsahan Perjanjian Jual Beli Online yang Dilakukan Anak di Bawah Umur dalam Perspektif Hukum Perikatan - Abdul Karnaen (Program Studi Ilmu Hukum, Universitas Kuningan, 2026)
The rapid development of digital technology has led to a significant increase in online buying and selling transactions involving various legal subjects, including minors. This phenomenon raises legal issues concerning the capacity to act in digital agreements and the legal consequences arising therefrom. This article aims to analyze the validity of online sale and purchase agreements entered into by minors under the law of obligations, as well as to examine the legal consequences and dispute resolution mechanisms that may arise. The research employs a normative legal research method using statutory and conceptual approaches. The findings indicate that online sale and purchase agreements made by minors do not fulfill the requirement of legal capacity as a subjective element under Article 1320 of the Indonesian Civil Code (KUHPerdata), rendering such agreements voidable (vernietigbaar). The legal consequences include the possibility of contract annulment, restoration of the parties to their original positions, and the emergence of certain civil liabilities while still considering the principle of child protection. Dispute resolution is primarily pursued through non-litigation mechanisms by emphasizing the principles of child protection and legal certainty.